Biodegradable nanocrystalline Mg-Zn-Ca-Ag alloys as suitable materials for orthopedic implants. (2022) - Ramya, M.; Ravi, K.R.
Abstract: Magnesium (Mg) based metallic glasses are gaining considerable attention as biodegradable implant materials, owing to their superior strength, elasticity and higher corrosion resistance than their crystalline counterparts. Though Mg-Zn-Ca based glassy alloys are showing improved performance than their crystalline counterparts, ideal corrosion rate about 0.02 mm/year (Song, 2007), for feasible orthopedic implants is yet to be achieved. Also, poor ductility of the glassy samples limits their practical usage as viable orthopedic implants. Hence, the key challenge in developing Mg based viable implant is to improve its corrosion resistance along with enhanced ductility. Nanocrystalline materials open possibilities for auxiliary improvements in strength and ductility. The aim of this work is to elucidate the influence of nanocrystalline structure and silver (Ag) alloying on in-vitro corrosion behaviour and mechanical properties of biodegradable Mg-Zn-Ca alloys. In this study, Mg66 Zn30 Ca4 and Mg64 Zn29 Ca5 Ag2 glass forming alloy have been chosen based on a thermodynamic model using P HHS parameter with pivotal effects of electron transfer effects, effect of atomic size mismatch and effect of randomness. In-vitro corrosion behaviour of Mg66 Zn30 Ca4 and Mg64 Zn29 Ca5 Ag25 in Simulated Body Fluid (SBF) solution analyzed using electrochemical studies showed that on a comparable scale, the corrosion resistance of nanocrystalline Mg64 Zn29 Ca5 Ag25 samples was greater than their amorphous Mg66 Zn30 Ca4 equivalents. Addition of Ag to Mg-Zn-Ca alloy leads to formation of corrosion influencing phases such as MgAg, Zn8 Ag5, MgZnAg2 along with oxides and hydroxides of Ag. Such phases contribute to improved corrosion resistance due to the formation of passive layer. The increase in hardness is credited to the lack of free volume in the nanocrystalline sample (Mg64 Zn29 Ca5 Ag2 ) in comparison to the amorphous sample (Mg66 Zn30 Ca4 ). The reported results demonstrate that Mg64 Zn29 Ca5 Ag2 acquiring the proper combination of mechanical properties and corrosion resistance can be further explored on antibacterial and cytocompatible perspectives in order to make them ideal bioimplant materials.